Favored decomposition paths of hydrogen sulfide at high pressure - Ting Ting Cui; Da Chen; Jian Chen Li; Wang Gao; Qing Jiang (New Journal of Physics, 2019)
Sulfur trihydride (H _3 S) is a theoretically predicted high-pressure superconductor and has been experimentally confirmed to have the highest superconducting transition temperature T _c . Solid H _2 S decomposition is considered as the primary source of H _3 S, however, it is complex and controversial how H _2 S is transformed into H _3 S. Herein, we employ the density functional theory augmented with many-body dispersion interactions (DFT+MBD) to study a full path of H _2 S decomposition at pressure of 20–260 GPa. We find that H _2 S starts to decompose into H _3 S and other H–S compounds from about 20 GPa, in which the MBD interactions can decrease both the phase transition pressure of H–S compounds and the reaction transition pressure of H _2 S decomposition. H _3 S _2 , H _4 S _3 , H _3 S _5 , sulfur and HS _2 are byproducts of H _2 S decomposition with increasing pressure. Our results provide a complete phase diagram of H–S compounds during H _2 S decomposition, and clarify the pressure range of each product and favored paths of H _2 S decomposition.